STATUS HARA FOSFOR DAN KALIUM DI LAHAN SAWAH DI KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Riza Agoesdy; Hamidah Hanum; Abdul Rauf; Fitra Syawal Harahap (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
This research was conducted in Tanjung Morawa Subdistrict of Deli Serdang Regency in May 2017 until August 2017. This research was a qualitative descriptive phenomenological research with land survey supported by qualitative laboratory analysis. Soil sampling was done at the survey area sequentially based on the location where the soil characteristics were different from the purposive random sampling method, so the result of soil analysis obtained was expected to reflect the actual value. The soil sampling was taken at the top layer at the top soil depth of 0 -20 cm, 60 cm and recording point coordinates by using GPS (global Positioning System). Soil chemical properties analyzed were P2O5 HCl 25% (mg 100 g-1); K2O HCl 25% (mg 100 g-1), and the status of P and K of rice field of Tanjung Morawa District., Rice field with medium P status was T Morawa B Village (20.20 mg 100 g-1), and that with low P status was Pardamean Village (6.34 mg 100 g-1), Wonosari (14.24 mg 100 g-1), Dalu XB (12,82 mg 100 g-1), andÂ Naga Timbul (9,51 mg 100 g-1). Rice field with high K status was Pardaeman Village (69,07 mg 100 g-1), and Dalu XB (69,07 mg 100 g-1 ). Rice filed with medium K status was Wonosari Village (27.43 mg 100 g-1). Rice field with low K status was. Morawa B (9,32 mg 100 g-1), and Naga Timbul (19,4 mg 100 g-1). P and K fertilization recommendation need to be corrected especially for soils having high P nutrient for efficient use of P fertilizer and eficcient farming. Rice straw needs to be returned to paddy field to increase K2O level of soil, in addition to K fertilizer K.